The Determinants of Dim Sum Bond Liquidity - Delitheou, Vasiliki; Lei , Meng; Verousis, Thanos (Archives of Business Research, 2020)
In this paper, we offer a comprehensive analysis of the structure of the Dim Sum bond market. We show that Dim Sum bonds usually have a short maturity and that the market is dominated by issuers from the banking sector. In our analysis of the determinants of Dim Sum bond bid-ask spread, we find that both bond-specific determinants (issuance amount, maturity, and collateral), and macroeconomic variables particular to the Dim Sum bond market, influence its liquidity. The narrower Chinese yuan interest rate gap between mainland China and Hong Kong and a growing appreciation of the Chinese yuan, in addition to the fall in the Dim Sum Bond Market Yield Index, have led to improved liquidity in the market.